Rapid degradation of Pseudomonas fluorescens 1‐aminocyclopropane‐1‐carboxylic acid deaminase proteins expressed in transgenic Arabidopsis. Issue 2 (6th June 2014) - Kim, Kangmin; Park, Sung‐Hee; Chae, Jong‐Chan; Soh, Byoung Yul; Lee, Kui‐Jae
Abstract 1‐Aminocyclopropane‐1‐carboxylate (ACC) deaminase is commonly produced by plant growth‐promoting rhizobacteria (PGPR) and has been suggested to facilitate the growth and stress tolerance of hosts via a reduction in levels of ethylene. However, the regulatory mechanism of ACC deaminase (AcdS) protein within host plant cells is largely unknown. Here, we demonstrated beneficial effects and post‐translational modification of PGPR‐originated AcdS proteins in plants. Compared with the wild‐type, transgenic Arabidopsis expressing the Pseudomonas fluorescens acdS (PfacdS) gene displayed increased root elongation and reduced sensitivity to 10 μM exogenous ACC, an ethylene precursor. Arabidopsis expressing PfacdS also showed increased tolerance to high salinity (150 mM NaCl). PfAcdS proteins accumulated in transgenic Arabidopsis were rapidly degraded, which was potentially mediated by the 26S proteasome pathway. The degradation of PfAcdS was alleviated in the presence of exogenous ACC. In conclusion, our data suggest that the plant growth‐promoting effects of bacterial AcdS proteins are potentially modulated via protein turnover inside the host plant cells. Such post‐translational modification plays a physiological role in the mutualistic interactions between microorganisms and plants in the rhizospheric and/or endospheric niche.